Multiuser macrodiversity detection in asynchronous DS-CDMA systems. - Welburn, L.R (IEEE Transactions on wireless communications)
The authors present a performance analysis for the reverse link of a wireless DS-code division multiple access (CDMA) system that exploits macrodiversity reception while adopting the maximum likelihood (ML) multiuser detector for the basic detection. This appears to be the first analytical treatment of the ML multiuser macrodiversity detector in asynchronous DS-CDMA systems. They also include the effects of frequency selective fading, imperfect synchronization, and imperfect channel state information. Power control and connection control companion algorithms are presented to assess the value of this detector in a system context. The authors have shown that the ML multiuser-macrodiversity detector is capable of reducing the bit-error rate for many users by several orders of magnitude compared with multiuser detectors that operate on each antenna separately.